An analysis of errors in English writings among undergraduates in UiTM Segamat Campus, Johore Branch - Muthusamy, Indrani A/P; Singh, Deepak Ratan; Daud, Dalila (Unit Penyelidikan dan Rundingan, 2004)
This study explores and analyses grammatical errors in English writing among undergraduates at the UiTM Johor Campus. The objective of the study is to investigate the types of grammatical errors made by students and to categorize them according to different grammatical components. The findings from this study can be used to adapt methods and techniques for the teaching and learning of the English language on campus. From a total population of 842 Part 2 Diploma students, 400 were randomly selected as participants for this study. Questionnaires regarding socio-demographic backgrounds and a writing task were administered to gather relevant data. It was found that grammatical errors seriously hampered the accuracy and fluency of students' essay writing. However, the suggestions and recommendations provided in this study aim to help students rectify these errors and enable them to be more proficient in their future writing performance.